Expeditious and solvent-free nickel-catalyzed C−H arylation of arenes and indoles - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2017)
An efficient solvent-free nickel-catalyzed method for C−H bond arylation of arenes and indoles has been developed, which proceeds expeditiously through chelation assistance. The reaction is highly selective for mono-arylation and tolerates sensitive and structurally diverse functionalities, such as halides, ethers, amines, indole, pyrrole and carbazole. This reaction represents the first example of a nickel-catalyzed C−H arylation by monochelate assistance and symbolizes a rare precedent in solvent-free C−H arylation. Mechanistic investigations by various controlled reactions, kinetic studies, and deuterium labeling experiments suggest that the arylation follows a single electron transfer (SET) pathway involving the turnover-limiting C−H nickelation process.

Expeditious and solvent-free nickel-catalyzed c-h arylation of arenes and indoles (vol 10, pg 2242, 2017) - Jagtap, Rahul A.; Soni, Vineeta; Punji, Benudhar (ChemSusChem, 2020)
Keywords: Arylation; C-H activation; heterocycles; Homogeneous catalysis; Nickel

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism